Análise zootécnica de sistemas de produção da pecuária de leite, na Zona da Mata, Minas Gerais - Teixeira Gomes , Sebastião; Coelho de Alvarenga , Sonia; Batista de Oliveira , Evonir (Revista Ceres, 2025)
This study deals with technical aspects of seven production systems previously identified in the dairy sector of three microregionsin the Zona da Mata, State ofMinas Gerais. It is based on arandom sample of 127 farms, and the data refer to 1974.